The Use of Promotional Tools in Enhancing Consumers’ Awareness towards the purchase of Agro-based Products - Islam, Hamidul; Sarker, Sahin Akter; Rodrick, Stanley Sumon (AIUB Journal of Business and Economics, 2019)
The necessity of modern retailing practices regarding marketing and sales of agro-based products in Bangladesh has resulted in enormous growth over the last few years. Therefore, this study explored the significance of promotional tools and benefits in growing young consumers’ awareness of agro-based products marketed by modern retail outlets in Dhaka city. It examined how these outlets have applied various tools of promotions to create awareness and transform consumers’ choice into purchase intention. Non-probability sampling especially convenience sampling technique was applied and around 260 responses were utilized to gather and analyze the reliable data. The data was collected using “survey” and secondary information was utilized to support the data. Responses were analyzed statistically with SPSS 20.0 using both descriptive and factor analysis tools. The findings showed that the significance of promotional tools and offers applied by these physical outlets are used to create awareness among the youths in Dhaka city is somewhat satisfactory. Consumers are having their highest priority towards the “Mobile and Telemarketing” tool whereas “Online and Social Media” tool received priority after the mentioned one. Therefore, the researchers opined that information about the effectiveness of these tools could enable modern retail outlets in Dhaka city to foster their competitiveness, ensure their long-term survival and boost their sales.